“I’m not sure what that means yet, but we’ll soon find out” – the discourse of newspaper live blogs - Tereszkiewicz, Anna (Studia Linguistica Universitatis Iagellonicae Cracoviensis, 2014)
The following paper focuses on newspaper live blogs. The aim of the analysis is to investigate the structure and discourse properties of this news format. The analysis examines the basic conventions concerning the form and content of these text types, including structural components of live blogs, multimedia, quoting and linking patterns, as well as discourse strategies used to underline “liveness”, interactivity and evaluation. The analysis proves that the discourse of live blogs constitutes an example of open structure news discourse, and reflects a blending of discourse properties typical of blogs as well as of broadcast and newspaper reporting.